Masters of War : Militarism and Blowback in the Era of American Empire (New York Routledge, 2003)
American dominion has begun breeding widespread dysfunction, resistance, and opposition likely to make the 21st century a time of sustained, generally unanticipated "blowback". This text reminds us that worldwide economic and military dominance has its price.
Include Index
Keywords: Militarism -- Military policy -- United States -- Diplomatic relations -- Diplomatic relations--Philosophy